(x+3)(x+4)+(x+6)(x-3)=

Simple and best practice solution for (x+3)(x+4)+(x+6)(x-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+3)(x+4)+(x+6)(x-3)= equation:


Simplifying
(x + 3)(x + 4) + (x + 6)(x + -3) = 0

Reorder the terms:
(3 + x)(x + 4) + (x + 6)(x + -3) = 0

Reorder the terms:
(3 + x)(4 + x) + (x + 6)(x + -3) = 0

Multiply (3 + x) * (4 + x)
(3(4 + x) + x(4 + x)) + (x + 6)(x + -3) = 0
((4 * 3 + x * 3) + x(4 + x)) + (x + 6)(x + -3) = 0
((12 + 3x) + x(4 + x)) + (x + 6)(x + -3) = 0
(12 + 3x + (4 * x + x * x)) + (x + 6)(x + -3) = 0
(12 + 3x + (4x + x2)) + (x + 6)(x + -3) = 0

Combine like terms: 3x + 4x = 7x
(12 + 7x + x2) + (x + 6)(x + -3) = 0

Reorder the terms:
12 + 7x + x2 + (6 + x)(x + -3) = 0

Reorder the terms:
12 + 7x + x2 + (6 + x)(-3 + x) = 0

Multiply (6 + x) * (-3 + x)
12 + 7x + x2 + (6(-3 + x) + x(-3 + x)) = 0
12 + 7x + x2 + ((-3 * 6 + x * 6) + x(-3 + x)) = 0
12 + 7x + x2 + ((-18 + 6x) + x(-3 + x)) = 0
12 + 7x + x2 + (-18 + 6x + (-3 * x + x * x)) = 0
12 + 7x + x2 + (-18 + 6x + (-3x + x2)) = 0

Combine like terms: 6x + -3x = 3x
12 + 7x + x2 + (-18 + 3x + x2) = 0

Reorder the terms:
12 + -18 + 7x + 3x + x2 + x2 = 0

Combine like terms: 12 + -18 = -6
-6 + 7x + 3x + x2 + x2 = 0

Combine like terms: 7x + 3x = 10x
-6 + 10x + x2 + x2 = 0

Combine like terms: x2 + x2 = 2x2
-6 + 10x + 2x2 = 0

Solving
-6 + 10x + 2x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '2'.
2(-3 + 5x + x2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-3 + 5x + x2)' equal to zero and attempt to solve: Simplifying -3 + 5x + x2 = 0 Solving -3 + 5x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '3' to each side of the equation. -3 + 5x + 3 + x2 = 0 + 3 Reorder the terms: -3 + 3 + 5x + x2 = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 5x + x2 = 0 + 3 5x + x2 = 0 + 3 Combine like terms: 0 + 3 = 3 5x + x2 = 3 The x term is 5x. Take half its coefficient (2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. 5x + 6.25 + x2 = 3 + 6.25 Reorder the terms: 6.25 + 5x + x2 = 3 + 6.25 Combine like terms: 3 + 6.25 = 9.25 6.25 + 5x + x2 = 9.25 Factor a perfect square on the left side: (x + 2.5)(x + 2.5) = 9.25 Calculate the square root of the right side: 3.041381265 Break this problem into two subproblems by setting (x + 2.5) equal to 3.041381265 and -3.041381265.

Subproblem 1

x + 2.5 = 3.041381265 Simplifying x + 2.5 = 3.041381265 Reorder the terms: 2.5 + x = 3.041381265 Solving 2.5 + x = 3.041381265 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + x = 3.041381265 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + x = 3.041381265 + -2.5 x = 3.041381265 + -2.5 Combine like terms: 3.041381265 + -2.5 = 0.541381265 x = 0.541381265 Simplifying x = 0.541381265

Subproblem 2

x + 2.5 = -3.041381265 Simplifying x + 2.5 = -3.041381265 Reorder the terms: 2.5 + x = -3.041381265 Solving 2.5 + x = -3.041381265 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + x = -3.041381265 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + x = -3.041381265 + -2.5 x = -3.041381265 + -2.5 Combine like terms: -3.041381265 + -2.5 = -5.541381265 x = -5.541381265 Simplifying x = -5.541381265

Solution

The solution to the problem is based on the solutions from the subproblems. x = {0.541381265, -5.541381265}

Solution

x = {0.541381265, -5.541381265}

See similar equations:

| 19=-(5x+7) | | 4(y-7)=5-(6y-2) | | C=39.45+0.25x | | 8z=3 | | 7(4x+2)=42 | | X^2-4x=5x | | 2.5k+5-1.5.5k=14 | | x^2+2x-363=0 | | 4x-8=7+3 | | v=Ixt | | z^3-z^2-6=0 | | 3y=0.006 | | 6=10c | | 1-5x=x-13 | | Log(x+4)=8 | | (2x)=1 | | Y-(-12)=7 | | 12x-6=-11x | | x^2-18x=1.25 | | 4(5x-8)-3(2x-7)= | | 9(9x)=96x | | 8x=(3x^2)-2 | | 7x-3=4x-24 | | (6f-k)= | | 36m^6+12m^4=m^2+0 | | 8r^2+10r-12=0 | | 10x+3=100 | | 5[3(x+4)-2(1-x)]-x-35=14x+65 | | 1.3-5r=7.8 | | 250x^3+128= | | 5y+6y-81=7y+102+66y | | 4a=3a+20 |

Equations solver categories